Three dimensional reconstruction of scenes from multiple views using active vision - Gibbs, Jonathon (2019)
The need to understand the mechanisms underlying the growth of plants and crops (plant phenotyping) is becoming increasingly important in society, particularly as the quantity of food and biofuel will need to double to meet the demands of the expanding global population, which is likely to exceed nine billion by 2050.